Housing and Health: Very Old People with Self-Reported Parkinson's Disease versus Controls. (26th March 2013) - Nilsson, Maria H.; Haak, Maria; Iwarsson, Susanne
Abstract : Objectives. To explore whether aspects of housing and health among very old people with self-reported Parkinson's disease (PD) differ from matched controls. Methods. Data from the ENABLE-AGE Survey Study were used to identify people with self-reported PD (n = 20 ) and three matched controls/individual (n = 60 ). The matching criteria were age (mean = 82 years), sex, country, and type of housing. The analyses targeted problems in activities of daily living, objective and perceived aspects of housing, for example, number of environmental barriers, accessibility (i.e., person-environment fit), and usability. Results. The number of physical environmental barriers did not differ (P = 0.727 ) between the samples. The PD sample had more (P < 0.001 ) accessibility problems than controls and perceived their homes as less (P = 0.003 ) usable in relation to activities. They were less independent and had more functional limitations (median 5 versus 2; P < 0.001 ), and 70% experienced loss of stamina or poor balance. Conclusions. Due to the fact that they have more functional limitations than very old people in general, those with self-reported PD live in housing with more accessibility problems. This explorative study has implications for rehabilitation as well as societal planning, but larger studies including people with a confirmed PD diagnosis are needed.